Polscy syndonolodzy. Z dziejów badań Całunu Turyńskiego i ich popularyzacji - Pilarczyk, Krzysztof (Collectanea Theologica, 2018)
The establishment of the Polish Center of Syndonology in Krakow in 2017, which is the delegation of the International Center of Syndonology in Turin, inspired the author to reflect on the Polish research on the Shroud of Turin. The article presents three generations of Polish syndonologists: major investigators of the shroud from the second half of the twentieth century and co-founders of the Syndonological Study in Krakow, created at the Polish Theological Society in 1981, and (3) the shroud researchers in the 21st century cooperating with the Polish Center of Syndonology. Their main research and educational achievements as well as participation in international fora were pointed out. The article is supplemented by Polish syndonological bibliography.